Variation of Spoken Slovene in the Case of Geographically Mobile Speakers - Maja Bitenc (Slovenščina 2.0: Empirične, aplikativne in interdisciplinarne raziskave, 2023)
Based on the pioneering variationist research on Slovene language material, the article explores the authentic language use of speakers of the Cerkno dialect who commute daily or weekly to work or school in Slovenia’s capital, Ljubljana. The research corpus comprises excerpts from informants’ full-day audio self-recordings, selected to represent variation of location, interlocutors, and conversation topic. Through a quantitative analysis of five phonological variables, the study reveals distinct language strategies with speakers of other varieties, resulting in a classification of one code-switcher, three code-mixers, and one dialect speaker language strategies employed by the informants when communicating with speakers of other varieties, resulting in a classification of code-switchers, code-mixers and dialect speakers. Furthermore, the qualitative data derived from interviews shed light on various sociopsychological aspects of the focal topic, such as the informants’ perception of their own speech behaviour, their experiences with language use, and their language attitudes, providing deeper insights into their language variability and highlighting the intricacies of language choice and interpersonal communication.